Start of experiments in the design configuration of the GOL-NB multiple-mirror trap. (1st August 2022) - Postupaev, V.V.; Batkin, V.I.; Burdakov, A.V.; Burmasov, V.S.; Ivanov, I.A.; Kuklin, K.N.; Lykova, Yu.A.; Melnikov, N.A.; Mekler, K.I.; Nikishin, A.V.; Polosatkin, S.V.; Rovenskikh, A.F.; et al.
Abstract: A multiple-mirror confinement is an alternative concept in fusion energy development that improves the particle and energy confinement times in open traps (linear magnetic systems). The paper discusses the development progress of the GOL-NB multiple-mirror experiment that was recently commissioned at BINP. The reference description of the GOL-NB hardware is presented. Properties of a low-temperature start plasma are discussed. The first results from test experiments with injection of one 25 keV neutral beam are shown. Methods of plasma stabilization in the non-min- B configuration are discussed. In general, the ongoing commissioning progress and results of the preliminary experiments are modestly optimistic for the expected device performance.